THE EFFECT OF TOTAL QUALITY MANAGEMENT ON THE PERFORMANCE OF SMEs THROUGH MEDIATION VARIABLE OF ORGANIZATIONAL COMMITMENT - Priyanka, Lidya; Setiawan, Margono (Jurnal Aplikasi Manajemen, 2017)
The purpose of this research is to analyze the impact of Total Quality Management (TQM) on Small-Medium Enterprise (SME) performance through organizational commitment mediation on tempeh chips SME in Sanan, Malang. The research use 30 SMEs sample as respondents, considerating SMEs with PIRT and Halal certificates, data analysis was done with WarpPLS 5.0. The research result show that TQM has positive significant impact on SME organisasional commitment. Organizational commitment has significant impact on SME performance. The result also show that the organizational commitment does not mediate the significant impact of TQM on SME performance.